Netralitas Birokrasi PNS Kabupaten Semarang pada Pemilukada Bupati dan Wakil Bupati Semarang Tahun 2015 - Fakih, Moh. (Faculty of Social Science, Universitas Negeri Semarang, 2018)
Bureaucracy political rights neutrality still needs to be done to see attitude and behavior of bureaucracy who impartial to one of candidate in Local Leaders Election at execution of Regional election of regent and vice regent onÃ‚Â December 9th, 2015 has well and safety held with winner polling is incumbent candidates as regent and vice regent of Semarang. General election as supporting facilities for democracy has arranged bureaucracy political rights neutrality, either to political party and also candidates (president, governor, Regent/Mayor), General Election Laws Number 32 Year of 2004 section 86 and section 76 and section 79, and Government Laws number 6 year 2005 section 61 and section 62, also with Laws Number 5 year 2014 section 87 article 4 item c. The purpose is: 1) To know candidates who entangles bureaucracy (functional and structural official in state official as participant and campaign expert in general elections of regent and vice regent of Semarang year 2015. 2) To know political rights neutrality in execution of regional election of regent and vice regent of Semarang year 2015. To reach the purpose, this research used qualitative descriptive method. Data analysis of Civil Servants Neutrality and involvement of bureaucracy official (Civil Servants) that becomes cause existence of opportunity to do collision in regional election for example: regional leader authority lifting, mutation, and discharge from and in 2nd echelon at local government specified by a regent after consulting to Governor (see government laws number 96 year 2000 and Laws Number 32 year 2004 section 130 article 2), then prohibition of candidates and neutral attitude of political rightsÃ‚Â have been arranged in the law and regulation with management of officer applies merit system bureaucracy. Research result which can be generalized collision of prohibition of involvement in campaign happened not done by Civil Servants and bureaucracy functionary in service country and position of politics rights of Civil Servants at neutral.